Wrocław’s episode of a well-known bookseller and publisher Roman Jasielski and his daughter Anna from Stanisławów - Werszler, Rafał (Folia Toruniensia, 2018)
Aim: The aim of the article is to show a very interesting episode of a bookseller and publisher from Stanisławów – Roman Jasielski and his daughter Anna, forcibly displaced after the Second World War. On the ground floor of the house Pod Złotą Palmą [English: Under the Golden Palm] in the space after the original Priebatsch bookshop in 1946, Jasielski created one of the first Polish bookshops in Wrocław. Research method: The article was written on the basis of the archival research of source documents, literature on the subject and from the on-site check of the existing building, which is currently the Lower Silesian Public Library under the name of Tadeusz Mikulski in Wrocław. Results/Conclusions: A short stay of Roman Jasielski and his daughter Anna, and at the same time his great passion and commitment for shaping Polish literature have left a significant mark among the bibliophilic communities in Lower Silesia. Their mission enabled the Pod Złotą Palmą house to continue to cultivate the bookselling and publishing tradition with a particular passion for the book. They became a very important link that united the prewar tradition of the history of the building at 58 Rynek in Wrocław with the present-day library.